2023
DOI: 10.1088/1674-1056/ace4b4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of thermal conductivities of cubic diamond, lonsdaleite, and nanotwinned diamond via machine-learned potential

Abstract: Diamond is a wide-bandgap semiconductor with a variety of crystal configurations, which has the potential for applications in the field of high-frequency, radiation-hardened, and high-power devices. There are several important polytypes of diamond, such as cubic diamond, lonsdaleite and nanotwinned diamond (NTD). The thermal conductivity of semiconductor should be calculated at different temperatures in high-power devices. However, there has been no potential reported for cubic diamond and its polytypes combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…In this work, cell structures were visualized using VESTA software . The model in this study was more than 130% larger than that in similar previous work. ,, Furthermore, convergence tests on the model size were conducted, and detailed information can be found in the Supporting Information. As a result, it could be shown that the size convergence was very good for the diamond and the β-Ga 2 O 3 model.…”
Section: Computational Methods and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, cell structures were visualized using VESTA software . The model in this study was more than 130% larger than that in similar previous work. ,, Furthermore, convergence tests on the model size were conducted, and detailed information can be found in the Supporting Information. As a result, it could be shown that the size convergence was very good for the diamond and the β-Ga 2 O 3 model.…”
Section: Computational Methods and Modelsmentioning
confidence: 99%
“…β-Ga 2 O 3 is regarded as a potential candidate for next-generation power devices due to the wide band gap of ∼4.9 eV and high breakdown electric field of 8 MV·cm –1 . The major barrier to the realization of high-power β-Ga 2 O 3 devices lies in the low thermal conductivity of ∼10 to 29 W·m –1 ·K –1 , , which usually results in heat dissipation issues. An excellent solution is the integration of the high thermal conductivity materials with the low ones to enhance heat dissipation. Diamond is a well-recognized promising candidate (>2000 W·m –1 ·K –1 ) for integration with β-Ga 2 O 3 . For example, Kim et al adhered n-type β-Ga 2 O 3 to p-type diamond through van der Waals interactions and achieved a p–n junction photodiode due to the most important factor that diamond nearly boasts the greatest heat dissipation properties compared with other materials .…”
Section: Introductionmentioning
confidence: 99%